Multisystem inflammatory syndrome (MIS-C) with SARS-CoV-2 omicron variant BA.2.38 in a four-year-old Chinese girl: A case report - Wang, Wen-yuan; Wang, Yong-jun; An, Cai-xia; Zhao, Qi-jun; Wang, Shu-ying; Li, Wan-yi; Yi, Bin; Li, Huan (Frontiers in Public Health, 2022)
We report a severe COVID-19 complicated with MIS-C in a girl treated by the author in China, and discuss the current research status and progress in the diagnosis and therapy of MIS-C in children. The patient was a 4-year-old child previously healthy who was referred to the hospital with a complaint of fever, finally, Multisystem inflammatory syndrome was diagnosed with COVID-19.